Characterization of sheet organic mulch produced from coconut fiber, water hyacinth, and banana pseudostem fiber combinations - Harahap, Nur Anisah Rizky; Nurhamiyah, Yeyen; Dewi, Ika Atsari; Jung, Young Hoon; Hamzah, Muhammad Hazwan bin; Rohma, Novita Ainur; Samudra, Rizki Putra; Pratama, Andhika Putra Agus; Lee, Yeon Ju; Suhartini, Sri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study developed a sheet-type organic mulch from coconut fiber, banana pseudostem, and water hyacinth without synthetic additives through drying, alkaline pretreatment in 1% NaOH solution for 30 minutes, pulping, molding, and oven-drying at 50 °C for 72 hours. The products were characterized for physical, mechanical, and chemical properties, including moisture and ash contents, water absorption capacity, tensile strength, and proximate, lignocellulosic, CNPK, FTIR, and SEM-EDX analyses. The raw materials showed distinct compositions: coconut fiber was rich in lignin (27.52%) and cellulose (37.87%), banana pseudostem had the highest hemicellulose (36.25%), and water hyacinth contained the greatest protein content (16.74%). Among treatments, M3P3 (70% coconut fiber: 30% banana pseudostem) exhibited the highest water absorption capacity (257.00%), while P1 (100% banana pseudostem) achieved the highest tensile strength (9.97 N). In contrast, E1 (100% water hyacinth) showed the highest moisture content (8.83%) but the lowest tensile strength (5.11 N). FTIR and SEM-EDX results confirmed the presence of hydroxyl and carbonyl functional groups and a porous surface morphology, supporting water retention and nutrient release. Overall, the composite mulch demonstrated eco-friendly, economical, and adaptive properties suitable for sustainable tropical agriculture applications.